EFFECT OF CYCLING ON CARDIOVASCULAR HEALTH ASSOCIATED WITH AGING PROCESS - Rynda, Rynda; Tanaka, Vidya M. Dewi; Qudsiyah, Inaroh; Maharani, Ni Ketut Ayu; Rachelia, Demak Vera; Notoprawiro, Nadia Carolina; Augusto, Kenny; Wulandari, Made Ayu Mirah; Juhanna, Indira Vidiari (Sport and Fitness Journal; Vol 10 No 1 (2022): Volume 10, No. 1, January 2022DO - 10.24843/spj.2022.v10.i01.p09, 2022)
ABSTRACT Cycling is a healthy exercise that can be enjoyed by people of all ages, from young children to older adults. Cycling have great attention from the health sector because of aiming to increase levels of physical activity. The main pathways between cycling and health under two perspectives generalizable evidence for health effects and specific impact modeling to quantify health impacts in concrete settings. Risks from air pollution can be assumed to be small, with limited evidence for cycling specific mechanisms. Physical activity, particularly cycling, is known to reduce the risk of cardiovascular diseases, slow down aging, and help in reducing weight and even stress. Keywords: cardiovascular, aging, stress, exercise, cycling